UPAYA MENINGKATKAN HASIL BELAJAR IPA MELALUI METODE MIND MAPPING PADA SISWA KELAS VI SD NEGERI TOTOGAN SAMIGALUH - Yusuf Nungky Diandita; Ana Fitrotun Nisa; Daimul Hasanah (UNIB Press, 2023)
The purpose of this study was to determine the improvement of science learning outcomes of grade VI students of SD Negeri Totogan through the application of the Mind Mapping method. The type of research was a class action research with the subject of research of grade VI students of SD Negeri Totogan totaling 24 students. Data collection methods used physics learning achievement test measurement tools on optical devices material, documentation, observation and interviews. This research used pretest-posttest design method. The analysis technique used in this research was t-test, namely paired sample t-test and independent sample t-test. Paired sample t-test was used to test the average difference (mean) between the pre-test and post-test results in each group (experimental group and control group). The research data were analyzed descriptively qualitatively and quantitatively. The results showed that learning through the application of the Mind Mapping method can improve science learning outcomes in grade VI students of SD Negeri Totogan. The improvement can be implemented through action modifications in the form of; delivery of material with a modified Mind Mapping method, question and answer material by involving students actively, making and creating Mind Mapping forms accompanied by teachers and researchers, presenting student Mind Mapping results by randomly selecting them, and reflecting on learning by involving students at the end of learning. Based on the test results, the learning outcome data showed that the average score in the pre-action was 61.67 with 16.7% learning completeness, increased in cycle I to 66.82 with 50% learning completeness, and increased again in cycle II with an average score of 83.19 with 79.2% learning completeness. Thus, we concluded that the Mind Mapping method can improve the learning outcomes of grade VI students of SD Negeri Totogan.